Reexamining the link between gender and corruption: The role of social institutions - Boris Branisa; Maria Ziegler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In this paper we reexamine the link between gender inequality and corruption. We review the literature on the relationship between representation of women in economic and political life, democracy and corruption, and bring in a new previously omitted variable that captures the level of discrimination against women in a society: social institutions related to gender inequality. Using a sample of developing countries we regress corruption on the representation of women, democracy and other control variables. Then we add the subindex civil liberties from the OECD Development Centre's GID Data-Base as the measure of social institutions related to gender inequality. The results show that corruption is higher in countries where social institutions deprive women of their freedom to participate in social life, even accounting for democracy and representation of women in political and economic life as well as for other variables. Our findings suggest that, in a context where social values disadvantage women, neither political reforms towards democracy nor increasing the representation of women in political and economic positions might be enough to reduce corruption.
Keywords: D63; D73; J16; 330; Social institutions; Gender inequality; Corruption; OECD Development Centre's GID Data-Base